Review of the leafhopper genus Evinus Dlabola (Hemiptera: Cicadellidae: Deltocephalinae) - Lu, Lin; Dietrich, Christopher H.; Zhang, Yalin (Zootaxa, 2013)
The leafhopper genus Evinus Dlabola (Deltocephalinae: Macrostelini) is reviewed. Seven new species are described including E. angulatus sp. nov., E. hainanensis sp. nov., E. longus sp. nov., E. obscurus sp. nov., E. planus sp. nov., E. sinuatus sp. nov. E. tenuis sp. nov. One previously described species, E. peri Anufriev, newly recorded from China, is redescribed. The species of the genus have so far been recorded from Iran, Tajikistan, Kyrgyzstan and China; here several new species from Thailand are added. A checklist and a key to species (males) are also provided.